The Effect of Contact Time of Javabark Adsorbent (Lannea coromandelica ( houtt.)merr) on Cd (II) Adsorption Capacity - Musrifah, Linda Ayu; Widwiastuti, Hanandayu; Asworo, Riska Yudhistia (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2026)
According to Indonesian Minister of Health Regulation No. 2 of 2023, the maximum limit for cadmium in bottled water is 0.003 mg/L. In this study, tannin biosorbents were used from the extraction of Javanese bark. Javanese bark contains tannin compounds that have the potential to bind heavy metals. This study aims to determine the effect of varying contact times of Java wood bark biosorbent on the adsorption capacity of Cd (II). The method used is an experiment to study the effect of contact time of Java wood bark biosorbent on the adsorbate. The contact times used for the Java wood bark biosorbent were 20, 40, 60, 80, 100, 120, 140, and 160 minutes. The residual Cd (II) concentration in the solution was determined using a UV-Vis spectrophotometer. The adsorption capacity of Cd (II) at contact times of 20, 40, 60, 80, 100, 120, 140, and 160 minutes was 0.073; 0.075; 0.078; 0.079; 0.116; 0.060, 0.052; 0.035 mg/g. From the results of the study, it can be concluded that the longer the contact time of the biosorbent in the adsorption of Cd (II) metal, the adsorption capacity will increase until it reaches the optimal contact time. After reaching the optimal contact time, adsorption decreases due to the desorption process. In this study, the optimal contact time for Java wood bark biosorbent was obtained at 100 minutes with an adsorption capacity of 0.116 mg/g. Keywords:Tannin;Cadmium;Adsorption;Biosorbent;Javabark;